SPATIAL AND TEMPORAL DISTRIBUTION OF CHLOROPHYL-A USING FLUORESENCE ANALYSIS IN INDONESIAN WATERS - Dika Praba P Cahya, Brian
Satellite is one of the tools used to detect the concentration of chlorophyll. In some coastal waters, there is a clear difference, where the product of the standard MODIS chlorophyll concentration is disturbed by colored dissolved organic matter (CDOM). By utilizing the fluorescence approach possessed by phytoplankton, it is expected to represent the concentration of chlorophyll near the coast more accurately. Data was obtained from the Aqua MODIS Level 2 satellite in 2016-2020 which consisted of chlorophyll MODIS, MODIS fluorescence data, rainfall data, and Cirebon waters observation data taken on 6 September 2020 and also observation data from other areas as additional data. The results of the comparison of chlor-FLH concentrations and observational data from case II waters (Cirebon and Delta Mahakam) resulted in a more accurate detection when compared to chlor-mod, with an average error for chlor-FLH (23%) and chlor-mod (125%). The concentration of chlorophyll-a in Indonesian waters has a high value in the case II area (near the coast and estuary) throughout the year. The average concentration of chlorophyll-a in the east monsoon (JJA) is 2.71 mg/m³ and is the highest compared to other seasons due to the upwelling phenomenon in southern Java to East Nusa Tenggara and western part of Sumatra, then the ENSO phenomenon also affects rainfall. rain in Indonesia as a whole which has an impact on increasing the concentration of chlorophyll-a with the difference in the concentration values of chlor-mod and chlor-flh at the mouth of the river due to the high concentration of CDOM